2014
DOI: 10.1038/srep04711
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Tomography

Abstract: Increasingly researchers are looking to bring together perspectives across multiple scales, or to combine insights from different techniques, for the same region of interest. To this end, correlative microscopy has already yielded substantial new insights in two dimensions (2D). Here we develop correlative tomography where the correlative task is somewhat more challenging because the volume of interest is typically hidden beneath the sample surface. We have threaded together x-ray computed tomography, serial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 33 publications
1
95
0
Order By: Relevance
“…17,18 State-of-theart characterisation techniques, such as X-ray computed tomography (X-ray CT), can provide non-destructive, in situ, information about the location, extent, and kinetics of damage evolution. 7,[17][18][19][20][21][22] Initial stages of localised corrosion and SCC can be visualised and quantified, with data providing the framework for life-time prediction models. 17,18,22 Corrosion characterisation so far has been limited to corrosion rate (CR) assessments derived from either electrochemical methods or weight loss measurements, which has become routine practice in quantifying aqueous CRs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 State-of-theart characterisation techniques, such as X-ray computed tomography (X-ray CT), can provide non-destructive, in situ, information about the location, extent, and kinetics of damage evolution. 7,[17][18][19][20][21][22] Initial stages of localised corrosion and SCC can be visualised and quantified, with data providing the framework for life-time prediction models. 17,18,22 Corrosion characterisation so far has been limited to corrosion rate (CR) assessments derived from either electrochemical methods or weight loss measurements, which has become routine practice in quantifying aqueous CRs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, leading work has been published integrating x-ray computed tomography, serial section FIB-SEM tomography, electron backscatter diffraction, and TEM elemental analysis on the same sample. 51 Such correlative multiscale tomography approaches can be extended to many fi elds and research problems. The article by Bradley and Withers describes the applications of this method toward structural biomaterials.…”
Section: In This Issuementioning
confidence: 99%
“…This technique was also used to observe pit formation and helped in the formation of pitting mechanism development in austenitic steel. High resolution (0.8 µm 3 voxel size) revealed that pitting corrosion shows intergranular corrosion due to low pH and high molarity of metal cations in the pit cavities [92]. …”
Section: (K) Additional Surface Investigating Technologiesmentioning
confidence: 99%